Knowledge translation in rehabilitation settings in low, lower-middle and upper-middle-income countries: a scoping review. Issue 2 (16th January 2023) - Regalado, I. C. R.; Lindquist, A. R.; Cardoso, R.; Longo, E.; Lencucha, R.; Hunt, M.; Thomas, A.; Bussières, A.; Boruff, J. T.; Shikako, K.
Abstract: Purpose: This review aims to identify the barriers and facilitators to knowledge use and Knowledge Translation (KT) strategies in rehabilitation in low, lower-middle, and upper-middle-income countries (LMICs). Materials and methods: A scoping review of studies of KT in rehabilitation in LMICs contexts using the Arksey and O'Malley Framework was conducted. A comprehensive search of MEDLINE and 10 other databases was undertaken to identify studies conducted primarily in LMICs. Results: From the initial 15.606 titles identified; 27 articles were included for final analysis. Our analysis identified the following themes: Professional culture and context; KT interventions; and the conceptualization and application of KT and Evidence Based Practice (EBP). Individual-level barriers to KT included lack of skills, knowledge about EBP and English language, lack of motivation, and decision-making power. Facilitators to KT included positive attitudes and motivation. Organization-level barriers included lack of time, lack of financial resources, limited access to scientific journals, and applicability of research to rural settings. Facilitators included adequate financial and physical resources, a supportive management environment, and the existence of training and continuing education programs. Conclusion: This review identified common and unique barriers and facilitators to KT in LMICs when compared to KT studies conducted in high-income settings. IMPLICATIONS FOR REHABILITATION: Knowledge Translation from academic institutions to rehabilitation clinical practice in low and upper-middle-income countries is important to support evidence-based practice and patient outcomes. Barriers at the individual level include professionals' ability to understand English and knowledge of the evidence-based practice. Organization-level barriers included lack of time to access and implement new practices, lack of financial and personal resources, limited access to scientific journals, and applicability of research to rural settings. Training and continuing education programs are needed to support rehabilitation professionals' efforts to achieve the application of evidence-based practice in clinical practice.